2011
DOI: 10.1128/jvi.02449-10
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Repression of C4 Complement by Hepatitis C Virus Proteins

Abstract: The fourth component of human complement (C4) plays an important role in innate immune function. C4 activity has been observed to be significantly lower in patients with chronic hepatitis C virus (HCV) infections, although the mechanism remains unknown. In this study, we have examined the mechanisms of C4 regulation by HCV. Liver biopsy specimens from patients with chronic HCV infections displayed significantly lower C4 mRNA levels than liver tissue samples from patients with unrelated liver disease. Further, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
66
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(73 citation statements)
references
References 34 publications
6
66
0
1
Order By: Relevance
“…Though likely not specific as markers of fibrosis progression, these signatures still reflect the gross alterations visible in this biofluid as a direct result of liver injury. Of specific relevance to HCV infection, however, is complement component 4A (C4A) which exhibited lower abundance in the SP and FP patient groups, consistent with recent papers that have shown it has significantly lower activity in HCV infected patients due to transcriptional repression by HCV proteins (24,25).…”
Section: Functional Classification and Comparison With Previoussupporting
confidence: 65%
See 1 more Smart Citation
“…Though likely not specific as markers of fibrosis progression, these signatures still reflect the gross alterations visible in this biofluid as a direct result of liver injury. Of specific relevance to HCV infection, however, is complement component 4A (C4A) which exhibited lower abundance in the SP and FP patient groups, consistent with recent papers that have shown it has significantly lower activity in HCV infected patients due to transcriptional repression by HCV proteins (24,25).…”
Section: Functional Classification and Comparison With Previoussupporting
confidence: 65%
“…All five proteins were detected with significant differential abundance in our analysis, and observed with the same expression trends. Additionally, markers such as C4A (24,25), LGALS3BP (31), HPX (32), A2M (32) have also been reported previously, and overlap with the current findings, as well as a vast majority of the serum proteins observed with significant differential abundance in a nonalcoholic fatty liver disease study (33). Due to the high sensitivity of the LC-IMS-MS measurements, we were able to detect significance of many proteins simultaneously that have only been observed as subsets in prior manuscripts.…”
Section: Functional Classification and Comparison With Previousmentioning
confidence: 99%
“…We have previously observed that C4 synthesis is mediated by USF-1 and IRF-1 transcription factors (24), and thus we examined whether cell-to-cell interaction affects the status of these transcription factors for C4 synthesis. IRF-1 was expressed at a modest level in untreated cells, while a dramatic recovery of IRF-1 and USF-1 was observed after coculture of IL-2-activated NK cells and hepatoma cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Hepatocytes in the liver are the primary host for HCV replication and are the main source for complement synthesis. We have previously identified C4 downregulation in hepatoma cells expressing HCV core or NS5A protein (24). NK cells play an important role in controlling viral hepatitis, liver fibrosis, and liver tumorigenesis and also contribute to the pathogenesis of liver injury and inflammation (25).…”
Section: Resultsmentioning
confidence: 99%
“…Specimens were collected from subjects with their written consent, and the human studies protocol (number 10592) was approved by the Saint Louis University Internal Review. RNA was prepared from liver specimens by using TRIzol (Invitrogen) as previously described (15). Commercially available control liver RNAs (Clontech, CA, and Lonza, NJ) were used for comparison.…”
Section: Methodsmentioning
confidence: 99%